(untitled) (Al-Academy, 2016)
Targeted research to study variations formalism in the paintings of the scratch -linear , and through surveys carried out by the researcher , found and to his knowledge that the study did not address the researchers before, this researcher found rationale in the study of plates scratch and identify variations of design in it. , Which included the first chapter of the research problem in question the following: What morphological variations in the paintings of the scratch -linear ?In order to reach solutions to this problem and to achieve results so research aims to identify the characteristics of the scratch for paintings , and design fundamentals and relationships , which are identified by the researcher Balentajat completed in all of Iraq , and TurkeyThe second chapter includes a brief history of the cut and scratch properties for paintings scratch and foundations relations and design The third chapter included the research community , which numbered (42)Chosen ones (3) samples were deliberate , the researcher has followed the descriptive approach drawing on form for analysis which is based on dialogue with several oversaw the validity of professors who specialize in the field either in the fourth quarter represents the analysis of samples , and to arrive at the results , including: -1 . - Diversity in terms of the formal properties of the panels included the adoption of the scratch plates scratch on the readability of the investigation by the communicative through lack of contention for text clips as in the sample (2) or fragmentation of the word into two parts due to the similarity of letters as in the sample (1,2) .2 . Adopt a regulatory approach relies on the concentration of readable text in the geometric center and the largest sizes and a contrasting color to the rest of the words of the total configuration as in the sample (1,2) .3 . - Plates are scratch organized directional whether the spatial organization inverted , which starts from left to right as in the sample ( 1.2 ) , or rely on the multiplicity of directions for occupancy spaces as in the sample (3)